Legal Perspectives for Cooperation of the Arctic States in the Development of Offshore Oil and Gas Resources in the Arctic - Dmitry K. Labin (Московский журнал международного права, 2016)
The article discusses the current legal framework of cooperation between the Arctic States in the development of offshore oil and gas resources in the Arctic and assesses the prospects for development of such cooperation.